Development and characterization of a low intensity vibrational system for microgravity studies - Omor M. Khan; Will Gasperini; Chess Necessary; Zach Jacobs; Sam Perry; Jason Rexroat; Kendall Nelson; Paul Gamble; Twyman Clements; Maximilien DeLeon; Sean Howard; Anamaria Zavala; et al. (npj Microgravity)
Abstract Extended-duration human spaceflight necessitates a better understanding of the physiological impacts of microgravity. While the ground-based microgravity simulations identified low intensity vibration (LIV) as a possible countermeasure, how cells may respond to LIV under real microgravity remain unexplored. In this way, adaptation of LIV bioreactors for space remains limited, resulting in a significant gap in microgravity research. In this study, we introduce an LIV bioreactor designed specifically for the usage in the International Space Station. Our research covers the bioreactor’s design process and evaluation of the short-term viability of cells encapsulated in hydrogel-laden 3D printed scaffolds under 0.7 g, 90 Hz LIV. An LIV bioreactor compatible with the operation requirements of space missions provides a robust platform to study cellular effects of LIV under real microgravity conditions.